Map of Nova Scotia, or Acadia : with the islands of Cape Breton and St. John’s, from actual surveys / by Captn. Montresor, engir. - Montresor, John, 1736-1799 (1768)
Nova Scotia --Maps --Early works to 1800. Acadia --Maps --Early works to 1800. Prince Edward Island --Maps --Early works to 1800. Prince Edward Island --Administrative and political divisions --Maps --Early works to 1800. Cape Breton Island (N.S.) --Maps --Early works to 1800. Color 1:390,000